(untitled) - Voyles, Bruce A. (Boston, 2002)
Rather than to present each taxonomic group of viruses in its entirety, the core of this book is organized around features of the reproductive cycle shared by all viruses. This concise, student-friendly text is intended for biology and microbiology majors and even beginning graduate students.
Keywords: Viruses,Vi rút học